High-purity aluminum oxide ceramic substrate and preparation process thereof

By adding magnesium oxide and zirconium oxide to high-purity alumina ceramic substrate and using a specific combination of adhesives and plasticizers, the problem of low bending strength of the ceramic substrate is solved, significantly improving its mechanical properties and thermal stability.

CN119462091AActive Publication Date: 2025-02-18SUZHOU JINGCI SUPER HARD MATERIALS

Patent Information

Application Number
CN202411647139.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The high-purity alumina ceramic substrate has low bending strength and is prone to fracture when subjected to bending loads.

Method used

By adding auxiliary materials such as magnesium oxide and zirconia, and using specific combinations of adhesives and plasticizers, the microstructure and mechanical properties of the ceramic substrate are improved.

Benefits of technology

The bending strength, fracture toughness and thermal stability of the alumina ceramic substrate are significantly improved, and the possibility of brittle fracture is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139954150000071
    Figure BDA0005139954150000071
  • Figure BDA0005139954150000081
    Figure BDA0005139954150000081
Patent Text Reader

Abstract

The invention relates to the technical field of electronic ceramic materials, and particularly discloses a high-purity aluminum oxide ceramic substrate and a preparation process thereof. The high-purity aluminum oxide ceramic substrate is prepared from the following raw materials in parts by weight: 0.20 to 0.25 part of magnesium oxide, 0.35 to 0.55 part of zirconium oxide, 1.2 to 1.5 parts of dispersing agent, 60 to 65 parts of ethanol, 99.7 to 99.8 parts of aluminum oxide, 12 to 15 parts of adhesive, 6 to 9 parts of plasticizer and 50 to 55 parts of n-butyl alcohol, the adhesive is a mixture of polyvinyl butyral, water glass and modified paraffin. The prepared high-purity aluminum oxide ceramic substrate has excellent chemical stability and mechanical strength, and the obtained aluminum oxide ceramic substrate has better density, mechanical property and thermal stability by mixing various raw material components, and is not easy to break when subjected to bending load.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic ceramic materials, and more specifically, to a high-purity alumina ceramic substrate and a preparation process thereof. Background Art

[0002] High-purity alumina ceramic substrate is a high-performance ceramic material made of high-purity alumina (Al2O3) as the main raw material through a specific molding and sintering process. High-purity alumina ceramic substrates have been widely used in the electronics industry due to their excellent mechanical, thermal and electrical properties, especially in the fields of electronic packaging, circuit substrates, power electronic devices and sensors.

[0003] Alumina ceramic substrates can be divided into different models according to the purity of alumina, such as 99 porcelain, 96 porcelain, 90 porcelain, etc., among which 99 porcelain means that the Al2O3 content is above 99%. The purity of high-purity alumina ceramic substrates directly affects their electrical and mechanical properties. The higher the purity, the higher the dielectric constant, the lower the dielectric loss, and the better the smoothness of the substrate.

[0004] Although the high-purity alumina ceramic substrate has high hardness and wear resistance, its brittle characteristics result in relatively low bending strength and it is easy to break when subjected to bending loads. Summary of the invention

[0005] In order to improve the problem of relatively low bending strength of alumina ceramic substrates, the present application provides a high-purity alumina ceramic substrate and a preparation process thereof.

[0006] In a first aspect, the present application provides a high-purity alumina ceramic substrate, which adopts the following technical solution: A high-purity alumina ceramic substrate, comprising the following raw materials, by weight: 0.20-0.25 parts of magnesium oxide, 0.35-0.55 parts of zirconium oxide, 1.2-1.5 parts of a dispersant, 60-65 parts of ethanol, 99.7-99.8 parts of aluminum oxide, 12-15 parts of an adhesive, 6-9 parts of a plasticizer, and 50-55 parts of n-butanol; The adhesive is a mixture of polyvinyl butyral, water glass and modified paraffin.

[0007] By adopting the above technical solution, magnesium oxide can be used as a sintering aid to improve the hardness, wear resistance and electrical insulation performance of the alumina ceramic substrate, reduce the sintering temperature of the alumina ceramic substrate, promote the bonding between grains, and improve the density of the material; magnesium oxide also has a lower thermal expansion coefficient, which can slow down the thermal expansion of the alumina ceramic substrate and improve its thermal stability. The addition of zirconium oxide can significantly improve the fracture toughness, hardness, wear resistance and thermal stability of the alumina ceramic substrate, improve the microstructure of the alumina ceramic substrate, refine the grains, reduce defects, and improve the bending strength.

[0008] Dispersants can reduce the surface energy between particles in the ceramic slurry, prevent particle agglomeration, ensure that particles are evenly dispersed in the slurry, and improve the stability of the slurry; the use of dispersants can improve the strength of the green body, making it less likely to deform or crack during drying and sintering, and promote the formation of dense and uniform substrates of alumina ceramic substrates, thereby improving mechanical properties (such as bending strength and fracture toughness) and electrical properties (such as dielectric constant, dielectric loss, and insulation strength). Ethanol and n-butanol can dissolve adhesives and plasticizers to obtain uniform slurry, which helps to disperse alumina powder particles and ensure the uniformity and stability of the slurry.

[0009] Alumina is the main component of alumina ceramic substrates, providing the basic structure and physical properties of the substrates. Binders play a supporting role in the molding process of alumina ceramic substrates, allowing the slurry to maintain its shape before drying and sintering, ensuring that the green body has sufficient strength, and can improve the fluidity and stability of the slurry, making it easier to mold. Plasticizers can reduce the viscosity of alumina ceramic slurry, making it easier to tape-cast, improve the stability of the slurry, prevent stratification or precipitation of the slurry during storage and processing, and ensure the uniformity and consistency of the slurry.

[0010] Among the adhesives, polyvinyl butyral plays a supporting role in the forming process of alumina ceramic substrates, allowing the slurry to maintain its shape before drying and sintering, promoting uniform shrinkage of alumina ceramic substrates, reducing cracking and deformation, and improving the density of sintered bodies. Water glass can improve the mechanical strength of alumina ceramic substrates, reduce the porosity of alumina ceramic substrates, and effectively improve the compressive strength. Polyvinyl butyral, as an organic adhesive, improves the fluidity and stability of the slurry, and provides good bonding strength and toughness. Water glass, as an inorganic adhesive, helps the dispersion of particles and the thixotropy of the slurry, and has good heat resistance and chemical stability. The mixture of the two can enhance the bonding properties of the material, improve the wet strength of the blank, and enhance the mechanical strength of the material. Modified paraffin has good fluidity and good compatibility, improves the plasticity of the material, and improves the mechanical properties during the forming process. It is mixed with polyvinyl butyral and water glass to ensure that the green body has sufficient strength, forms a network structure during the drying process, enhances the mechanical strength of the blank, and makes it less likely to be damaged during the forming and handling process.

[0011] Optionally, the mass ratio of the polyvinyl butyral, water glass and modified paraffin is 1:0.5-0.7:0.2-0.4.

[0012] By adopting the above technical scheme, the mass ratio of polyvinyl butyral, water glass and modified paraffin is further limited within a certain range, so as to improve the mechanical strength of the alumina ceramic substrate. Polyvinyl butyral plays a supporting role, so that the slurry maintains its shape before drying and sintering. Water glass can improve the mechanical strength of the alumina ceramic substrate and effectively improve the compressive strength. The modified paraffin has good fluidity and good compatibility, so that the polyvinyl butyral and water glass are mixed evenly, and the mechanical strength of the ceramic substrate is subsequently improved, so that it is not easily damaged during the molding and processing process.

[0013] Optionally, the preparation method of the modified paraffin wax comprises the following steps: heating the paraffin wax to melt at 60-65° C., adding sodium dodecylbenzene sulfonate, modified carbon fiber and carboxymethyl cellulose under stirring, stirring at 80-85° C. for 3-4 hours, and cooling to obtain the modified paraffin wax.

[0014] By adopting the above technical scheme, sodium dodecylbenzene sulfonate can improve the dispersibility of modified carbon fiber and methyl cellulose in paraffin, so that the paraffin system is mixed evenly. The modified carbon fiber has high strength and high modulus. After mixing with paraffin, the mechanical properties of the system, such as tensile strength, flexural strength and impact resistance, can be enhanced. Carboxymethyl cellulose can improve the viscosity and formability of paraffin, so that paraffin and modified carbon fiber are mixed evenly, and the stability of the paraffin system is improved. It is subsequently applied to alumina ceramic substrates to enhance the bonding force between ceramic powders, improve the mechanical strength of green bodies, reduce surface cracks, and reduce the breakage rate during transportation and processing.

[0015] Optionally, the mass ratio of the paraffin wax, the modified carbon fiber and the carboxymethyl cellulose is 1:0.3-0.5:0.1-0.2.

[0016] By adopting the above technical solution, the mass ratio of paraffin wax, modified carbon fiber and carboxymethyl cellulose is further limited within a certain range, thereby improving the viscosity and mechanical properties of paraffin wax. The modified carbon fiber has high strength and high modulus. After mixing with paraffin wax, it can enhance the mechanical properties of the paraffin system such as tensile strength, flexural strength and impact resistance. Carboxymethyl cellulose can improve the viscosity and formability of paraffin wax, so that paraffin wax and modified carbon fiber are mixed evenly, and subsequently applied to alumina ceramic substrates to enhance the bonding force between ceramic powders, improve the mechanical strength of green bodies, reduce surface cracks, and reduce the breakage rate during transportation and processing.

[0017] Optionally, the method for preparing the modified carbon fiber comprises the following steps: grinding short carbon fibers with a length of 40-45 μm for 15-17 h to reduce the length of the short carbon fibers to below 0.5 μm, dispersing the short carbon fibers in deionized water, adding talcum powder and nano-silicon dioxide, stirring at a temperature of 70-75°C for 1-2 h, and drying to obtain modified carbon fibers.

[0018] By adopting the above technical scheme, the short carbon fibers have high strength and wear resistance, and can improve the mechanical properties of the ceramic substrate, such as the flexural strength and fracture toughness. The talcum powder can be loaded on the surface of the short carbon fibers to improve the mechanical strengths, such as the flexural strength and compressive strength of the short carbon fibers. Nano-silicon dioxide has high strength and wear resistance, and can be loaded on the surface of the short carbon fibers and talcum powder to improve the strength and toughness of the modified carbon fibers. It will be subsequently applied to alumina ceramic substrates to improve the strength and toughness of alumina ceramic substrates.

[0019] Optionally, the mass ratio of the short carbon fiber, talcum powder and nano-silicon dioxide is 1:0.2-0.4:0.07-0.09.

[0020] By adopting the above technical scheme, the mass ratio of short carbon fibers, talcum powder and nano-silicon dioxide is further limited within a certain range, thereby improving the strength and toughness of the carbon fibers. Talc powder can be loaded on the surface of short carbon fibers, and nano-silicon dioxide can be loaded on the surface of short carbon fibers and talcum powder. The combination of short carbon fibers, talcum powder and nano-silicon dioxide improves the mechanical strengths of carbon fibers, such as bending strength, compressive strength and toughness. The carbon fibers are subsequently applied to alumina ceramic substrates to improve the strength and toughness of the alumina ceramic substrates, reduce brittle fracture, and further improve the density and strength of the alumina ceramic substrates.

[0021] Optionally, the aluminum oxide is an aluminum oxide powder with a purity of ≥99.9%, and an average particle size D50 of the aluminum oxide is 0.3-0.4 μm.

[0022] By adopting the above technical solution, the purity and particle size of alumina are limited, which helps to form a more uniform sintered body and reduce the deformation and cracking of the alumina ceramic substrate.

[0023] Optionally, the dispersant is at least one of polyacrylamide, polycarboxylate ammonium salt, and stearic acid.

[0024] By adopting the above technical solution, the dispersant can prevent the particles in the ceramic slurry from agglomerating, ensure that the particles are evenly dispersed in the slurry, and improve the stability of the slurry.

[0025] Optionally, the plasticizer is at least one of polyethylene, dioctyl phthalate, and polyethylene glycol.

[0026] By adopting the above technical solution, the plasticizer can reduce the viscosity of the alumina ceramic slurry, improve the stability and fluidity of the slurry, prevent the stratification or precipitation of the slurry during storage and processing, and ensure the uniformity and consistency of the slurry.

[0027] In the second aspect, the present application provides a preparation process for a high-purity alumina ceramic substrate, comprising the following steps: mixing magnesium oxide, zirconium oxide, a dispersant, alumina and ethanol, grinding to obtain a slurry, then adding an adhesive, a plasticizer and n-butanol, mixing and grinding to obtain a tape-casting slurry, degassing, tape-casting and debinding the tape-casting slurry, and sintering at a high temperature of 1480-1500°C to obtain a high-purity alumina ceramic substrate.

[0028] By adopting the above technical solution, the method is simple to operate, and the obtained high-purity alumina ceramic substrate has good mechanical strength and stability.

[0029] In summary, this application has the following beneficial effects: 1. In the present application, magnesium oxide improves the hardness, wear resistance and electrical insulation properties of the alumina ceramic substrate, reduces the sintering temperature of the alumina ceramic substrate, promotes the bonding between grains, and improves the density of the material; magnesium oxide also has a lower thermal expansion coefficient, which can slow down the thermal expansion of the alumina ceramic substrate and improve its thermal stability; the addition of zirconium oxide can significantly improve the fracture toughness, hardness, wear resistance and thermal stability of the alumina ceramic substrate, improve the microstructure of the alumina ceramic substrate, refine the grains, reduce defects, and improve the bending strength.

[0030] 2. The dispersant in the present application can reduce the surface energy between particles in the ceramic slurry, prevent particle agglomeration, ensure that the particles are evenly dispersed in the slurry, and improve the stability of the slurry; the adhesive plays a supporting role in the forming process of the alumina ceramic substrate, so that the slurry maintains its shape before drying and sintering, ensures that the green body has sufficient strength, and can improve the fluidity and stability of the slurry, making it easier to form.

[0031] 3. In the present application, polyvinyl butyral plays a supporting role in the forming process of the alumina ceramic substrate, so that the slurry maintains its shape before drying and sintering, promotes uniform shrinkage of the alumina ceramic substrate, reduces cracking and deformation, and improves the density of the sintered body; water glass can improve the mechanical strength of the alumina ceramic substrate, and has good heat resistance and chemical stability; modified paraffin has good fluidity and good compatibility, improves the plasticity of the material, improves the mechanical properties during the forming process, and is mixed with polyvinyl butyral and water glass to ensure that the green body has sufficient strength, forms a network structure during the drying process, enhances the mechanical strength of the body, and makes it not easily damaged during the forming and handling process. DETAILED DESCRIPTION

[0032] Preparation example of modified paraffin wax Preparation Example 1-1 The preparation method of modified paraffin wax comprises the following steps: heating and melting 200g paraffin wax at 65°C, adding 10g sodium dodecylbenzene sulfonate, modified carbon fiber and carboxymethyl cellulose under stirring, stirring at 85°C for 4h, and cooling to obtain modified paraffin wax.

[0033] The mass ratio of paraffin wax, modified carbon fiber and carboxymethyl cellulose is 1:0.3:0.1.

[0034] The preparation method of modified carbon fiber comprises the following steps: grinding 100 g of short carbon fiber with a length of 40-45 μm for 17 hours to reduce the length of the short carbon fiber to below 0.5 μm, then dispersing it in 200 mL of deionized water, adding talcum powder and nano-silicon dioxide, stirring at a temperature of 75° C. for 2 hours, and drying to obtain modified carbon fiber.

[0035] The mass ratio of short carbon fiber, talcum powder and nano-silicon dioxide is 1:0.4:0.09.

[0036] Preparation Example 1-2 The difference from Preparation Example 1-1 is that the carbon fiber is not modified.

[0037] Preparation Example 1-3 The difference from Preparation Example 1-1 is that carboxymethyl cellulose is not added.

[0038] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of paraffin wax, modified carbon fiber and carboxymethyl cellulose is 1:0.5:0.2.

[0039] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of paraffin wax, modified carbon fiber and carboxymethyl cellulose is 1:0.1:0.6.

[0040] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no talc is added in the preparation method of the modified carbon fiber.

[0041] Preparation Example 1-7 The difference from Preparation Example 1-1 is that in the preparation method of the modified carbon fiber, no nano-silicon dioxide is added.

[0042] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of short carbon fiber, talcum powder and nano-silicon dioxide is 1:0.2:0.07.

[0043] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of short carbon fiber, talcum powder and nano-silicon dioxide is 1:0.6:0.15. Example

[0044] Example 1 A high-purity alumina ceramic substrate, comprising the following raw materials: 0.20 g of magnesium oxide, 0.35 g of zirconium oxide, 1.2 g of dispersant, 60 g of ethanol, 99.8 g of aluminum oxide, 12 g of adhesive, 6 g of plasticizer, and 50 g of n-butanol; The adhesive is a mixture of polyvinyl butyral, water glass and modified paraffin.

[0045] The mass ratio of polyvinyl butyral, water glass and modified paraffin is 1:0.5:0.2.

[0046] The alumina is alumina powder with a purity of ≥99.9%, and the average particle size D50 of the alumina is 0.3-0.4 μm.

[0047] The dispersant is polyacrylamide.

[0048] The plasticizer is polyethylene.

[0049] A preparation method of a high-purity alumina ceramic substrate comprises the following steps: mixing magnesium oxide, zirconium oxide, a dispersant, alumina and ethanol, grinding for 8 hours to obtain a slurry, then adding an adhesive, a plasticizer and n-butanol, mixing and grinding for 30 hours to obtain a tape-casting slurry, subjecting the tape-casting slurry to degassing, tape-casting and binder removal, and sintering at a high temperature of 1500°C to obtain a high-purity alumina ceramic substrate.

[0050] Specifically, the above-mentioned tape-casting slurry is pressed into a degassing tank, and the vacuum stirring principle is used to remove bubbles and remove part of ethanol and n-butanol. After degassing, the solid content of the slurry is 78-79%, and the slurry viscosity is 15000cps. The degassed slurry is pressed into the material trough of the tape-casting machine, and the tape-casting rate is 0.5m / min to obtain a tape-casting green tape with a thickness of 0.32mm. The tape-casting green tape is cut to obtain a tape-casting green body. The tape-casting green body is debonded in a debinding furnace to obtain a debonded sheet. The debonded sheet is sintered at a high temperature of 1500°C for 65min to obtain a high-purity alumina ceramic substrate.

[0051] The modified paraffin wax was prepared in Preparation Example 1-1.

[0052] Example 2 A high-purity alumina ceramic substrate, which differs from Example 1 in that it includes the following raw materials: 0.25g magnesium oxide, 0.55g zirconium oxide, 1.5g dispersant, 65g ethanol, 99.7g aluminum oxide, 15g adhesive, 9g plasticizer, and 55g n-butanol.

[0053] The mass ratio of polyvinyl butyral, water glass and modified paraffin is 1:0.7:0.4.

[0054] Example 3 A high-purity alumina ceramic substrate, which is different from Example 1 in that the mass ratio of polyvinyl butyral, water glass and modified paraffin is 1:0.1:0.9.

[0055] Example 4 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax adopts Preparation Example 1-2.

[0056] Example 5 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared in Preparation Example 1-3.

[0057] Example 6 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared as in Preparation Example 1-4.

[0058] Example 7 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared in Preparation Example 1-5.

[0059] Example 8 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared in Preparation Example 1-6.

[0060] Example 9 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared in Preparation Example 1-7.

[0061] Example 10 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared in Preparation Example 1-8.

[0062] Embodiment 11 A high-purity alumina ceramic substrate, which differs from Example 1 in that the modified paraffin wax is prepared in Preparation Example 1-9.

[0063] Comparative Example Comparative Example 1 A high-purity alumina ceramic substrate, which is different from Example 1 in that water glass is not added to the adhesive.

[0064] Comparative Example 2 A high-purity alumina ceramic substrate, which differs from Example 1 in that no modified paraffin is added to the adhesive.

[0065] Performance testing The high-purity alumina ceramic substrates prepared in Examples 1-11 and Comparative Examples 1-2 were subjected to performance tests in accordance with GB / T14619-2013.

[0066] Sintering density: The instrument model used is: MZ-A600; Bending strength: The three-point bending test method is used to test the bending strength of the material using a universal testing machine. f , sample size: l×b×h=30mm×3mm×5mm, span is 30mm, and the pressure head descent rate is 0.5mm / min.

[0067] Fracture toughness: The fracture toughness of the material was measured by the single-edge notched beam method (SENB method) using a WDW electronic universal testing machine at a loading rate of 0.05 mm / min.

[0068] Breakdown strength: The breakdown strength was tested using a voltage breakdown tester, wherein a laser-scribed Φ35 mm wafer was silver-plated on both sides with a thickness of 1.5±0.5 mm. The test results are shown in Table 1.

[0069] Table 1 Test data of embodiments and comparative examples Combining the examples and the data in Table 1, it can be seen that the high-purity alumina ceramic substrates prepared in Examples 1-2 have good density and mechanical properties. The density of Example 1 is 3.98 g / cm 3 , the flexural strength is 531.3MPa, and the fracture toughness is 6.56MPa﹒ m 1 / 2 , the breakdown strength is 26.9kv / mm. This shows that the high-purity alumina ceramic substrate prepared in this application has good mechanical properties such as bending strength, and the alumina ceramic substrate obtained by mixing various raw material components has good density, mechanical properties and thermal stability, and is not easy to break when subjected to bending load during subsequent use.

[0070] Example 3 changes the mass ratio of polyvinyl butyral, water glass and modified paraffin, and comparative examples 1-2 do not add water glass and modified paraffin, respectively. As can be seen from Table 1, the density, flexural strength, fracture toughness and breakdown strength of Example 3 are worse than those of Examples 1-2, but are significantly better than those of Comparative Examples 1-2, indicating that water glass can improve the mechanical strength of the alumina ceramic substrate and effectively improve the compressive strength. The modified paraffin has good fluidity and good compatibility, so that the polyvinyl butyral and water glass are evenly mixed, and the mechanical strength of the ceramic substrate is subsequently improved, so that it is not easily damaged during the molding and processing process.

[0071] In the preparation method of modified paraffin in Example 4, modified carbon fiber is not added, and in the preparation method of modified paraffin in Example 5, carboxymethyl cellulose is not added. In Examples 6-7, the mass ratio of paraffin, modified carbon fiber and carboxymethyl cellulose is changed. As can be seen from Table 1, the density, flexural strength, fracture toughness and breakdown strength of Examples 4-5 are better than those of Example 3, but worse than those of Examples 1-2. The density, flexural strength, fracture toughness and breakdown strength of Example 7 are better than those of Examples 4-5, but worse than those of Examples 1-2, indicating that the modified carbon fiber has high strength and high modulus. After mixing with paraffin, the mechanical properties of the paraffin system such as tensile strength, flexural strength and impact resistance can be enhanced. Carboxymethyl cellulose can improve the viscosity and formability of paraffin, so that paraffin and modified carbon fiber are evenly mixed, and subsequently applied to alumina ceramic substrates to enhance the bonding force between ceramic powders, improve the mechanical strength of the green body, reduce surface cracks, and reduce the breakage rate during transportation and processing.

[0072] In the preparation method of modified carbon fiber in Example 8, talcum powder is not added, in the preparation method of modified carbon fiber in Example 9, nano-silicon dioxide is not added, and the mass ratio of short carbon fiber, talcum powder and nano-silicon dioxide is changed in Examples 10-11. As can be seen from Table 1, the density, flexural strength, fracture toughness and breakdown strength of Examples 8-9 are better than those of Example 4, but worse than those of Examples 1-2. The density, flexural strength, fracture toughness and breakdown strength of Example 11 are better than those of Examples 8-9, but worse than those of Examples 1-2, indicating that talcum powder can be loaded on the surface of short carbon fiber, and nano-silicon dioxide can be loaded on the surface of short carbon fiber and talcum powder. The combination of short carbon fiber, talcum powder and nano-silicon dioxide improves the mechanical strength of carbon fiber such as flexural strength, compressive strength and toughness, and is subsequently applied to alumina ceramic substrates to improve the strength and toughness of alumina ceramic substrates, reduce brittle fracture, and further improve the density and strength of alumina ceramic substrates.

[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-purity alumina ceramic substrate, characterized in that: The raw materials include: by weight, 0.20-0.25 parts of magnesium oxide, 0.35-0.55 parts of zirconium oxide, 1.2-1.5 parts of dispersant, 60-65 parts of ethanol, 99.7-99.8 parts of aluminum oxide, 12-15 parts of adhesive, 6-9 parts of plasticizer, and 50-55 parts of n-butanol; The adhesive is a mixture of polyvinyl butyral, water glass and modified paraffin.

2. A high-purity alumina ceramic substrate according to claim 1, characterized in that: The mass ratio of the polyvinyl butyral, water glass and modified paraffin is 1:0.5-0.7:0.2-0.

4.

3. A high-purity alumina ceramic substrate according to claim 1, characterized in that: The preparation method of the modified paraffin comprises the following steps: heating the paraffin at 60-65° C. to melt, adding sodium dodecylbenzene sulfonate, modified carbon fiber and carboxymethyl cellulose under stirring, stirring at 80-85° C. for 3-4 hours, and cooling to obtain the modified paraffin.

4. A high-purity alumina ceramic substrate according to claim 3, characterized in that: The mass ratio of the paraffin wax, the modified carbon fiber and the carboxymethyl cellulose is 1:0.3-0.5:0.1-0.

2.

5. A high-purity alumina ceramic substrate according to claim 4, characterized in that: The preparation method of the modified carbon fiber comprises the following steps: grinding short carbon fibers with a length of 40-45 μm for 15-17 hours to reduce the length of the short carbon fibers to less than 0.5 μm, dispersing the short carbon fibers in deionized water, adding talcum powder and nano-silicon dioxide, stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain the modified carbon fibers.

6. A high-purity alumina ceramic substrate according to claim 5, characterized in that: The mass ratio of the short carbon fiber, talcum powder and nano-silicon dioxide is 1:0.2-0.4:0.07-0.

09.

7. The high-purity alumina ceramic substrate according to claim 1, characterized in that: The aluminum oxide is an aluminum oxide powder with a purity of ≥99.9%, and an average particle size D50 of the aluminum oxide is 0.3-0.4 μm.

8. The high-purity alumina ceramic substrate according to claim 1, characterized in that: The dispersant is at least one of polyacrylamide, polycarboxylate ammonium salt and stearic acid.

9. The high-purity alumina ceramic substrate according to claim 1, characterized in that: The plasticizer is at least one of polyethylene, dioctyl phthalate and polyethylene glycol.

10. The method for preparing a high-purity alumina ceramic substrate according to claim 1, characterized in that: The method comprises the following steps: mixing magnesium oxide, zirconium oxide, a dispersant, aluminum oxide and ethanol, grinding to obtain slurry, then adding an adhesive, a plasticizer and n-butanol, mixing and grinding to obtain a tape-casting slurry, degassing, tape-casting and debinding the tape-casting slurry, and sintering at a high temperature of 1480-1500°C to obtain a high-purity aluminum oxide ceramic substrate.

Citation Information

Patent Citations

  • High-hardness wear-resistance aluminum oxide ceramic and preparation method of same

    CN105236939A

  • High-voltage-resistant insulating positioning ceramic material

    CN111875359A

  • Preparation method of high-toughness aluminum oxide ceramic

    CN114478041A

  • High-purity ultrathin high-strength aluminum oxide ceramic substrate as well as preparation method and application thereof

    CN114538900A

  • High-purity high-strength aluminum oxide ceramic substrate and preparation method thereof

    CN115849885A

Cited By

  • Multilayer ceramic substrate and preparation method thereof

    CN119735429A

  • A multi-layer ceramic substrate and a preparation method thereof

    CN119735429B

  • High-strength ceramic taking aluminum tailings as raw material and preparation method of high-strength ceramic

    CN120398513A

  • Insulating aluminum oxide multilayer ceramic substrate and preparation method thereof

    CN120903919A

  • Insulating alumina multilayer ceramic substrate and method for manufacturing the same

    CN120903919B